Mining and Biosynthesis of Bioactive Lanthipeptides From Microorganisms - Li, Caiyun; Alam, Khorshed; Zhao, Yiming; Hao, Jinfang; Yang, Qing; Zhang, Youming; Li, Ruijuan; Li, Aiying (Frontiers in Bioengineering and Biotechnology, 2021)
Antimicrobial resistance is one of the most serious public health issues in the worldwide and only a few new antimicrobial drugs have been discovered in recent decades. To overcome the ever-increasing emergence of multidrug-resistant (MDR) pathogens, discovery of new natural products (NPs) against MDR pathogens with new technologies is in great demands. Lanthipeptides which are ribosomally synthesized and post translationally modified peptides (RiPPs) display high diversity in their chemical structures and mechanisms of action. Genome mining and biosynthetic engineering have also yielded new lanthipeptides, which are a valuable source of drug candidates. In this review we cover the recent advances in the field of microbial derived lanthipeptide discovery and development.